EFFECT OF GREEN MARKETING MIX ON GREEN CUSTOMER SATISFACTION AND LOYALTY IN KATHMANDU VALLEY - Sah, Gunja Kumari; Shah , Ghanshyam Prasad (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
In recent years, sustainability has become a key factor in determining customer satisfaction and loyalty. In real terms, customers have demonstrated a favorable willingness to pay for sustainable solutions, including eco-friendly and eco-efficient goods and services. So, this research examines the impact of the green marketing mix on customer satisfaction and loyalty. This study also investigates the mediating effect of green customer satisfaction on customer loyalty. The study employed a quantitative research design and collected primary data through a structured questionnaire using a purposive sampling method from 340 green marketing customers in the Kathmandu Valley. The raw data were imported into the Statistical Package for the Social Sciences software to present demographic status and examine the internal factor structure reliability using exploratory factor analysis. Next, a measurement model and structural equation model were used to convert information into comprehensive knowledge by the Analysis of Moment Structure software. The results show that green marketing mix components are significant in predicting green customer satisfaction (H4: β = 0.146, p < 0.05) but are insignificant in predicting green customer loyalty (H5: β = 0.002, p > 0.05). However, the research also reveals a significant mediating effect of green customer satisfaction on loyalty (H6: β = 0.205, p < 0.05). The direct impact of green product value, price, and social media information is momentous in the green marketing mix. Incorporating a green marketing mix approach into a business’s overall marketing plan can impressively benefit environmentally conscious enterprises in the Kathmandu Valley by ensuring their customers remain loyal and satisfied. JEL Classification Codes: M31, Q56, M14.